Association between decreased respiratory function and increased blood pressure variability. Issue 2 (April 2018) - Imaizumi, Yuki; Eguchi, Kazuo; Hoshide, Satoshi; Kario, Kazuomi
Abstract : Objective: The respiratory system is an important component in the control of the autonomic nervous system, and is a possible factor of blood pressure variability (BPV). We examined whether decreased respiratory function is associated with exaggerated BPV in hypertensives. Patients and methods: This is a substudy of the Japan Morning Surge-Home Blood Pressure Study and patients who underwent both spirometry and ambulatory blood pressure monitoring (ABPM) in the Japan Morning Surge-Home Blood Pressure study were analyzed. In 95 hypertensives without known clinical respiratory diseases, we performed ABPM and the respiratory function test. Results: Percent vital capacity (%VC), but not forced expiratory volume in 1 s as a percentage of forced vital capacity, was associated with the SD ( r =−0.23, P <0.05) and coefficient of variation ( r =−0.25, P <0.05) of daytime systolic blood pressure (SBP). Lower %VC was associated with higher SD of daytime SBP ( P =0.049 for trend). After adjusting for covariates, %VC tended to be associated with SD of daytime SBP ( β =−0.22, P =0.08) and was associated with coefficient of variation of daytime SBP ( β =−0.26, P =0.04). Conclusion: Decreased respiratory function was associated with exaggerated ambulatory BPV, especially in the daytime in hypertensives without respiratory diseases. This is the first study to show an association between respiratory function and increased BPV as assessed by ABPM. The results of our study indicate that low respiratory function could exaggerate BPV, and thus may be one of the mechanisms underlying the elevated cardiovascular risk in patients with decreased respiratory function. Abstract : Supplemental Digital Content is available in the text.